Potencial do trans-cinamaldeído como adjuvante natural de meropenem contra biofilme de isolados nosocomiais de acinetobacter baumannii multirresistentes - Sampaio, Francisca Antônia Nauriana Araújo (2024)
Multi-resistant (MDR) Acinetobacter baumannii has emerged worldwide as an important cause of hospital infections with high mortality rates, being a critical global clinical problem due to the limitation of therapeutic alternatives for its treatment. Thus, the combination of the vast mechanisms of antimicrobial resistance and its ability to survive in the hospital environment makes A. baumannii a potential nosocomial pathogen. This context drives growing interest in new therapeutic approaches, such as trans-cinnamaldehyde (TC) – a substance derived from plant metabolism – as a basis for the development of new antimicrobials. The objective of this study was to evaluate the potential of TC as a natural adjuvant to meropenem (MPN) against biofilm of nosocomial isolates of Acinetobacter baumannii MDR. For this, the collected samples were initially subjected to a disk diffusion test in agar and microdilution in broth. The kinetics were evaluated based on subinhibitory combinations of the antibiotic with TC, as wel l as the effect of antibiofilm activity. The disk diffusion results produced an inhibition halo between 32.33 and 39.66 mm. The minimum inhibitory concentration (MIC) for all strains was 500 µg/mL, the same value presented for minimum bactericidal concentr ation (MBC). There was also an increase in the antimicrobial potential with a synergistic effect in the TC/MPN combinations. Finally, the combination of TC with MPN showed a significant interference in the pre-formed biofilm of A. baumannii MDR, showing an effective action on this pathogen as a proposal to use it in the development of new products, whether as a medicine or those intended to hospital disinfection, bringing promising results for public health.